Youth‐focused group mindfulness‐based intervention in individuals with early psychosis: A randomized pilot feasibility study. Issue 4 (15th October 2018) - MacDougall, Arlene G.; Price, Elizabeth; Vandermeer, Matthew R. J.; Lloyd, Chantelle; Bird, Richelle; Sethi, Rickinder; Shanmugalingam, Aturan; Carr, Jason; Anderson, Kelly K.; Norman, Ross M. G.
Abstract : Aim: To assess the feasibility of a randomized pilot trial that evaluated the acceptability and potential clinical utility of the Mindfulness Ambassador Program (MAP), a unique, standardized 12‐session facilitated group mindfulness‐based intervention (MBI) for youth experiencing early psychosis. Methods: Twenty‐one patients of an early psychosis intervention program were randomized to receive MAP (n  = 11) or treatment as usual ( n  = 10). Acceptability was measured by group attendance rate and client satisfaction; feasibility of the study design was measured by the recruitment and retention rate. The means, standard deviations, and 95% confidence intervals were described for outcomes of interest. Results: MAP is associated with a high degree of acceptability and has beneficial effects for depression and fatigue. The randomized trial design is feasible. Conclusions: This study provides important pilot data supporting a larger randomized trial of effectiveness for MAP as a group MBI for early psychosis. Details of MAP and study limitations are discussed.